Circulating Irisin and Myostatin as Markers of Muscle Strength and Physical Condition in Elderly Subjects - Planella-Farrugia, Cristina; Comas, Ferran; Sabater-Masdeu, Mònica; Moreno, María; Moreno-Navarrete, José María; Rovira, Oscar; Ricart, Wifredo; Fernández-Real, José Manuel (Frontiers in Physiology, 2019)
Background and objective: Aging is a physiological process known to produce changes in body composition, affecting the musculature and leading to decreased muscle strength. Muscle in response to exercise acts as an endocrine organ, producing and releasing myokines such as irisin and myostatin that modulate muscular growth. Here, we aimed to evaluate the effects of low intensity resistance exercise, with or without protein supplementation, on body composition, anthropometric parameters and circulating irisin and myostatin in elderly subjects. Methods: This is a prospective and controlled clinical trial in which subjects were randomized into 3 groups: 1) control group (n=20), 2) low intensity resistance exercise group (RE) (n=14) and 3) low intensity resistance exercise and nutritional support group (RENS) (n=9). Participants, aged 60-75 years, were studied at baseline and 16 weeks thereafter. Body composition was evaluated through bioelectric impedance. Serum irisin and myostatin was measured using ELISA. Results: At follow-up, RENS resulted in a significant increase in fat free mass (47.4±7.4 vs 46.5±7.4, p=0.046), the calf muscle circumference (36.4±1.3 vs 32.3±4.3, p=0.025) and circulating irisin (3±1.1 vs 2.6±1.3, p=0.030) compared to baseline. RE resulted in a significant increase in grip strength (17.2±4.6 vs 15.3±4.6, p=0.011) and irisin (3.1±0.8 vs 2.4±0.3, p=0.011) and decreased walking speed at different distance (p<0.02). Opposite findings in these parameters were observed in control intervention. In line with these findings, the percent change of calf muscle circumference (p=0.003) and fat free mass (p<0.0001) were significantly increased in RENS compared to control, whereas fat mass (p=0.033) was decreased. Interestingly, in this group, strength was positively correlated with fat free mass (r= 0.782, p=0.008), and circulating irisin was significantly decreased in those participants with strength loss at the end of the study (p=0.002). No significant correlation between circulating irisin and myostatin in any group was observed. Conclusion: Circulating irisin, but not myostatin, constitutes a marker for improved muscular performance in elderly subjects.